The history and present of public drinking water supply and its regionalisation in Debrecen - Nagy, Sándor (Acta Agraria Debreceniensis, 2013)
The public water supply played a major role in the urbanization of Debrecen city, just like in the case of many other cities. We had plenty of water and so we wasted it. However nowadays we experience a considerable decrease in the level of groundwater which causes an increasing need of energy for pumping. Beside the above mentioned the ecological threat and the decreasing water quality are also major problems. This study attempts to draw attention to the possibilities and the future of the regional water supply, by showing the history of the water supply, the sanitation systems of Debrecen and their present day activities.